Strength and uniformity of EICP-treated sand under multi-factor coupling effects - Jianwei Zhang; Yue Yin; Wanpeng Shi; Hanliang Bian; Lei Shi; Luyuan Wu; Zhiguang Han; Junjie Zheng; Xiang He (Biogeotechnics)
Enzyme-induced carbonate precipitation (EICP) is an environment-friendly method for improving soil mechanical properties. The extraction and application of plant crude urease reduces the treatment cost. However, in terms of the efficiency of calcium carbonate production and cementation, crude urease is considered inferior to pure urease or urease bacteria. In this paper, urease extracted from soybean was used to explore the effects of urease activity, treatment method, number of treatments (NTs), injection rate, and curing time on the unconfined compressive strength and calcium carbonate distribution characteristics of EICP-treated sand. The results showed that, compared with the pre-mixing method and the two-phase method, the one-phase method produced higher strength and a more uniform distribution of calcium carbonate. The cementation efficiency decreased with the increase of urease activity. The high-rate injection can improve the treatment effect of high-activity urease. Under the same cementation level, high strength and calcium carbonate cementation efficiency can be achieved by one-phase-low-activity EICP treatment. Data Availability Statement: All data, models, and code generated or used during the study appear in the submitted article.